RNaseT2 knockout rats exhibit hippocampal neuropathology and deficits in memory - Kerstin W. Sinkevicius; Thomas R. Morrison; Praveen Kulkarni; Martha K. Caffrey Cagliostro; Sade Iriah; Samantha Malmberg; Julia Sabrick; Jennifer A. Honeycutt; Kim L. Askew; Malav Trivedi; Craig F. Ferris (The Company of Biologists, 2018)
RNASET2 deficiency in humans is associated with infant cystic leukoencephalopathy, which causes psychomotor impairment, spasticity and epilepsy. A zebrafish mutant model suggests that loss of RNASET2 function leads to neurodegeneration due to the accumulation of non-degraded RNA in the lysosomes. The goal of this study was to characterize the first rodent model of RNASET2 deficiency. The brains of 3- and 12-month-old RNaseT2 knockout rats were studied using multiple magnetic resonance imaging modalities and behavioral tests. While T1- and T2-weighted images of RNaseT2 knockout rats exhibited no evidence of cystic lesions, the prefrontal cortex and hippocampal complex were enlarged in knockout animals. Diffusion-weighted imaging showed altered anisotropy and putative gray matter changes in the hippocampal complex of the RNaseT2 knockout rats. Immunohistochemistry for glial fibrillary acidic protein (GFAP) showed the presence of hippocampal neuroinflammation. Decreased levels of lysosome-associated membrane protein 2 (LAMP2) and elevated acid phosphatase and β-N-acetylglucosaminidase (NAG) activities indicated that the RNASET2 knockout rats likely had altered lysosomal function and potential defects in autophagy. Object recognition tests confirmed that RNaseT2 knockout rats exhibited memory deficits. However, the Barnes maze, and balance beam and rotarod tests indicated there were no differences in spatial memory or motor impairments, respectively. Overall, patients with RNASET2 deficiency exhibited a more severe neurodegeneration phenotype than was observed in the RNaseT2 knockout rats. However, the vulnerability of the knockout rat hippocampus as evidenced by neuroinflammation, altered lysosomal function and cognitive defects indicates that this is still a useful in vivo model to study RNASET2 function.